ANALISIS KINERJA KEUANGAN BANCO NACIONAL DE COMERCIO DE TIMOR LESTE - Soares da Cruz, Maculada (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.10.TAHUN 2014, 2014)
Writing in this thesis, analyzing the financial performance of the Banco National de Comercio de Timor Leste (BNCTL). The method used in this study is the CAMEL method includes Capital, Asset Quality, Earning Ability and likuidity. The management aspect is not analyzed because it memfocuskan the financial aspects alone. The data used is BNCTL financial statements in the period 2009-2013. Results Analysis of financial performance (BNCTL) during the period 2009-2013 be seen from the analysis of CAR with the average ratio of 21.08%, with an average PPAP ratio of 125.58%, with an average ROA ratio of 3, 71%, with an average ROA ratio of 80.54%, with an average LACLR ratio of 30.85% and a LDR with an average ratio of 87.91%, so that the Bank's financial performance relatively healthy. In view of the quality of earning assets ratio (KAP) during the period 2009 to 2013 obtained an average ratio of 28.64%, so it is still classified as Not Healthy.
Keywords: Analysis Of Financial Performance De Banco Nacional De Comercio East Timor